4 - Le secteur informel une réalité à réexplorer: ses rapports avec les institutions et ses capacités développantes: by Abdoulaye Niang - Abdoulaye Niang (Africa Development, 1996)
This paper analyses the informal sector concept by integrating legitimity and legality variables, as well as its relations with the modern and traditional sectors. It comes out of this analysis a classification of informal sector activities according to criteria of survival, subsistence, promotion and transition towards the modern sector.